(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
• Formation of the primitive heart tube it starts from week 3 of gestation period. It’s origin is from splanchnic mesoderm where the two endocardial tube fuse together to form a single primitive heart tube.There are 5 segments which is from cranial to caudal : Truncus arteriosus,bulbus cordis,primitive ventricle,primitive atrium,sinus venosus.If any deviation occurs in these segments it can lead to complex congenital heart disease (CHD).